Triglyceride to HDL-C Ratio is Associated with Insulin Resistance in Overweight and Obese Children - Iwani, N.A.K.Z.; Jalaludin, M.Y.; Zin, R.M.W.M.; Fuziah, M.Z.; Hong, J.Y.H.; Abqariyah, Y.; Mokhtar, A.H.; Wan Nazaimoon, W.M. (Nature Publishing Group, 2017)
The purpose of this study was to investigate the usefulness of triglyceride to hdl-c ratio (TG:HDL-C) as an insulin resistance (IR) marker for overweight and obese children. A total of 271 blood samples of obese and overweight children aged 9-16 years were analysed for fasting glucose, lipids and insulin. Children were divided into IR and non-insulin resistance, using homeostasis model assessment (HOMA). The children were then stratified by tertiles of TG: HDL-C ratio. The strength between TG:HDL-C ratio and other parameters of IR were quantified using Pearson correlation coefficient (r). Odds ratio was estimated using multiple logistic regression adjusted for age, gender, pubertal stages and IR potential risk factors. Children with IR had significantly higher TG:HDL-C ratio (2.48) (p = 0.01). TG:HDL-C ratio was significantly correlated with HOMA-IR (r = 0.104, p < 0.005) and waist circumference (r = 0.134, p < 0.001). Increasing tertiles of TG:HDL-C ratio showed significant increase in mean insulin level (p = 0.03), HOMA-IR (p = 0.04) and significantly higher number of children with acanthosis nigricans and metabolic syndrome. The odds of having IR was about 2.5 times higher (OR = 2.47; 95% CI 1.23, 4.95; p = 0.01) for those in the highest tertiles of TG:HDL-C ratio. Hence, TG:HDL-C may be a useful tool to identify high risk individuals.